Mapping Malory - Armstrong, D. author. aut Link
XII, 232 p. 9 illus.
Keywords: Medievalists are increasingly grappling with spatial studies. This timely book argues that geography is a crucial element in Sir Thomas Malory's M orte Darthur and contributors shine a light on questions of politics and genre to help readers better understand Malory's world.